The National Security Agency and the William F. Friedman Collection. Issue 3 (4th May 2017) - Sherman, David
ABSTRACT: In addition to being one of the founders of modern American cryptology, William Friedman was a noted cryptologic historian who amassed a major collection of cryptologic literature and artifacts in both his personal and official files. Drawing on over 50, 000 pages of documents newly released by the National Security Agency and other sources, this article places the man, his career, and his collections in the context of the government's changing secrecy policies of the early Cold War to offer new insights into Friedman's sometimes fraught relationship with that agency, its efforts to influence the amount and nature of cryptologic information in the public domain, and a series of confrontations over his personal and private papers.